RETRACTED: Justification of anti-crisis measures in the management of dairy cattle breeding based on mathematical modeling - Babkina Anastasia; Puchkova Olga; Svetlova Galina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001